Localized Increment and Decrement in the Total Electron Content of the Ionosphere as a Response to the April 20, 2018, Geomagnetic Storm - Carlos Sotomayor-Beltran (International Journal of Geophysics)
A moderate geomagnetic storm occurred on April 20, 2018. Using vertical total electron content (VTEC) maps provided by the Center for Orbit Determination in Europe, ionospheric responses to the geomagnetic storm could be identified in generated two-dimensional differential VTEC maps. During the day of the storm the enhancement of the equatorial ionization anomaly (EIA), product of the super-fountain effect was identified. A localized TEC enhancement (LTE) was also observed to the south of the EIA on April 20, 2018. It was also possible to visualize this LTE in a longitudinal section of the EIA as a third crest. The maximum increment of VTEC for the LTE was 204%. This LTE is quite unique because it happened during the expected solar cycle 24 and 25 minimum, and according to a previous study no LTE observation could be done for the last solar two-cycle minimum. The origin of the observed LTE is suggested to be partly product of the super-fountain effect. Finally, a localized TEC decrement (LTD) was observed towards the end of the day, April 20, 2018. Because this LTD consisted in the disappearance of the northern and southern crests of the EIA and this occurred during the recovery phase of the geomagnetic storm, it can be suggested that the LTD origin is due to the westward disturbance electric field. This mechanism was put forward by a past study that also analyzed the responses to a geomagnetic storm (the 2015 St. Patrick’s day storm), being one of the responses the inhibition of both crests of the EIA.